Novel Copolymer of Diisopropyl Fumarate and Benzyl Acrylate Synthesized Under Microwave Energy and Quasielastic Light Scattering Measurements - Oberti, Tamara Gisela (2010)
Microwave assisted free radical copolymerization of diisopropyl fumarate (DIPF) and benzyl acrylate (BzA) with different copolymer compositions was performed using benzoyl peroxide as initiator. The effect of the reaction conditions on the macromolecular characteristics, monomer reactivity ratio and copolymer properties were studied. The monomer conversion and average molecular weights increase with the content of BzA units in the copolymer. The copolymers were characterized by IR, ¹H and ¹³C-NMR spectroscopies and the molecular weights were analyzed with size exclusion chromatography (SEC). The reactivity ratios obtained from an extended Kelen-Tüdös method under microwave irradiations are a factor which is double than those obtained by thermal copolymerization. The product r₁r₂ = 0.152 suggests a preference of both propagating macroradicals toward consecutive homopolymerization. The hydrodynamic and polydispersity size were measured in ethylacetate, tetrahydrofuran and methylethylketone with a quasi-elastic light scattering (QELS) technique showing that the quality of the solvents increases in the order: EA < THF < MEK.